2015
DOI: 10.3892/ol.2015.3724
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced hepatitis B virus reactivation in hepatocellular carcinoma: A case report

Abstract: Abstract. Hepatitis B virus (HBV) reactivation associated with radiotherapy is rare. The present study reports the case of a 46-year-old man that experienced fatal HBV reactivation. The patient suffered from hepatocellular carcinoma (HCC) with portal vein tumor thrombus, which was treated by radiotherapy at a daily fraction of 2 Gy over 5 weeks, up to a total radiation dose of ~50 Gy. The patient presented with fatigue, yellow sclera and abdominal distension ~8 weeks subsequent to the administration of radioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Radiotherapy is also believed to be a risk factor of HBV reactivation. Radiotherapy was reported to induce HBV reactivation in patients with hepatocellular carcinoma of the liver (37,38). A previous study suggested that radiation-induced liver toxicity with HBV reactivation arises from a bystander effect on irradiated endothelial cells releasing cytokines (39).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is also believed to be a risk factor of HBV reactivation. Radiotherapy was reported to induce HBV reactivation in patients with hepatocellular carcinoma of the liver (37,38). A previous study suggested that radiation-induced liver toxicity with HBV reactivation arises from a bystander effect on irradiated endothelial cells releasing cytokines (39).…”
Section: Discussionmentioning
confidence: 99%
“…4 The present study found that several antitumor treatments, including TACE, RFA, MWA, PEI, and brachytherapy, were associated with HBV reactivation, which is associated with recurrence of HCC and OS, consistent with previous reports. [19][20][21][22][23] Combining antiviral treatment with conventional antitumor therapy is significantly associated with a reduced HBV reactivation. 24,25 When treating liver cancer (eg, by TACE), some patients developed hepatitis B flares, and their risk was reduced by the use of antiviral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic and the Baseline Clinical Characteristics B Virus DNA Level and Hepatocellular Carcinoma Recurrence nonstandard treatment group, and 2.89 (1.26) cm in the standard treatment group (P < .001).Hepatitis B virus DNA levels of more than 10 5 copies/mL were found in 40.6% of the no treatment group, 20.9% of the nonstandard treatment group, and 10.8% of the standard treatment group and levels of 10 5 copies/mL or less in 59.4% in the no treatment group, 79.1% in the nonstandard treatment group, and 89.2% in the standard treatment group. AFP levels greater than 400 ng/mL (to convert to micrograms per milliliter, multiply by 1) were found in 78.2% of the no treatment group,23.3% of the nonstandard treatment group, and 21.5% of the standard treatment group and of 400 ng/mL or less in 21.8% of the no treatment group, 76.7% of the nonstandard treatment group, and 78.5% of the standard treatment group (P < .001). Child-Pugh stage A was found in 74.4% in the no treatment group, 74.4% of the nonstandard treatment group, and 72.3% of the standard treatment group and B in 25.6% of the no treatment group, 25.6% of the nonstandard treatment group, and 27.7% of the standard treatment group.…”
mentioning
confidence: 98%
“…Moreover, of six HBV carriers that developed RILD, four showed evidence of HBV reactivation, with two of them progressing to liver failure [ 84 ]. Other investigators have reported HBV reactivation after liver irradiation with 3D-CRT, with one study suggesting that IL-6 produced from endothelial cell damage was implicated in HBV reactivation through bystander effect [ 40 , 85 ]. A prospective study that enrolled 205 patients with HCC demonstrated that concurrent, more intensive therapies and higher HBV DNA levels (>10 4 copies/ml) were independent predictors of HBV reactivation, ultimately recommending prophylactic antiviral therapy for all patients with high levels of HBV DNA, irrespective of the modality chosen for HCC treatment [ 86 ].…”
Section: Introductionmentioning
confidence: 99%